A Lower Bound on the Critical Momentum of an Impurity in a Bose–Einstein Condensate - Hinrichs, Benjamin; Lampart, Jonas (Comptes Rendus. Mathématique)
In the Bogoliubov–Fröhlich model, we prove that an impurity immersed in a Bose–Einstein condensate forms a stable quasi-particle when the total momentum is less than its mass times the speed of sound. The system thus exhibits superfluid behavior, as this quasi-particle does not experience friction. We do not assume any infrared or ultraviolet regularization of the model, which contains massless excitations and point-like interactions.